2022
DOI: 10.1186/s12912-022-01106-7
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ knowledge and attitudes toward patient-controlled analgesia for postoperative pain control in a tertiary hospital in South Korea

Abstract: Background This study investigated the knowledge and attitude of surgical ward nurses toward patient-controlled analgesia (PCA) to develop educational material for nurses on the use of PCA. Methods This study was a cross-sectional study comprising 120 nurses from eight surgical wards in a tertiary hospital in South Korea. A questionnaire addressing 6 domains of knowledge of and attitudes towards PCA was conducted over 1 week and analyzed using desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…They observed that nurses who received PCA education had noticeably better attitudes than those who did not. Additionally, older nurses with more clinical expertise had a more positive outlook on PCA (13). In this study, the rate of hearing PCA expression was 83.7% after the course.…”
Section: Discussionmentioning
confidence: 56%
“…They observed that nurses who received PCA education had noticeably better attitudes than those who did not. Additionally, older nurses with more clinical expertise had a more positive outlook on PCA (13). In this study, the rate of hearing PCA expression was 83.7% after the course.…”
Section: Discussionmentioning
confidence: 56%